A study of UPCD Department of Community Dentistry's community-based program in barangay 883, Sta. Ana Manila 2005-2007 - Beltran, Christian M.
The Department of Community Dentistry of the University of the Philippines College of Dentistry (UPCD) aspires of respond to the changing needs and demands of a community's oral health by implementing oral health care programs appropriate to these needs. In line with this, a 3-year community-based program was implemented at Barangay 883, Sta Ana, Manila. Oral examination was performed by the UPCD clinicians on the residents annually in order to monitor changes in their oral health status. Their records include DMFT/dmft score, OHI-S index, and interviews regarding their oral health practices. This study aimed to describe the oral health status of the residents of Barangay 883 Sta. Ana Manila who participated in the three-year community-based program for the year 2005, 2006 and 2007. Data were gathered by reviewing the records of the residents for the three years. From one hundred (100) residents, only thirteen (13) completed the three year program. They were then divided into three (3) groups according to their age. Data which include DMFT/dmft scores, OHI-S indices, and oral health practices were tabulated and described accordingly. Analysis of data showed a general decrease in the participants' dmft/DMFT scores from 2005 to 2007, except for those belonging to Group 2. On the other hand, the OHI-S of the participants increased from 2005 to 2007. Improvement on their oral health practices can also be noted. An immediate apparent change in the oral health status of the residents of Brgy. 883, Sta Ana, Manila is not evident as shown by small modifications in their mean dmft/DMFT scores and OHI-S indices and their oral health practices.